Identification and Biosynthesis of New Acyloins from the Thermophilic Bacterium Thermosporothrix hazakensis SK20‐1T. Issue 4 (28th January 2014) - Park, Jin‐Soo; Kagaya, Noritaka; Hashimoto, Junko; Izumikawa, Miho; Yabe, Shuhei; Shin‐ya, Kazuo; Nishiyama, Makoto; Kuzuyama, Tomohisa
Abstract Two new acyloin compounds were isolated from the thermophilic bacterium Thermosporothrix hazakensis SK20‐1T. Genome sequencing of the bacterium and biochemical studies identified the thiamine diphosphate (TPP)‐dependent enzyme Thzk0150, which is involved in the formation of acyloin. Through extensive analysis of the Thzk0150‐catalyzed reaction products, we propose a putative reaction mechanism involving two substrates: 4‐methyl‐2‐oxovalerate as an acyl donor and phenyl pyruvate as an acyl acceptor.